The ‘moral panics’ behind television advertising regulations in Malaysia - Mokhtar, Aida (2010)
The bloody racial riot of 13 May 1969 marked the underlying animosity between the dominant cultural groups which had been developing for some time in Malaysia (Mohamad, 1970). The National Cultural Policy 1971, by defining a common Malaysian culture, was the catalyst used by the government to bind the predominantly Malay, Chinese and Indian ethnicities. Establishing peace through commonality is important to achieve the government’s vision of a developed Malaysia in its own ‘mould’ in the year 2020 or Vision 2020 (Mohamad, 1991). Television advertisements in Malaysia are made to portray images of the Malaysian culture and promote a common roof between different ethnicities by the country’s television advertising regulatory authorities (Frith, 1987). In relation to this, the study attempted to examine the television advertising regulatory framework in Malaysia with the dearth of previous research studies. It focused on understanding ‘what’ decisions were made by regulatory authorities when approving television advertisements for Malaysian television and ‘why’. A thematic analysis on interviews with key regulatory authorities found that they based their decisions on the moral panics (intense concerns) of Malaysian viewers as defined by the ‘grassroots model’ (Goode and Ben-Yehuda, 1994). Malaysian viewers believe that television advertisements can affect behaviour and are most concerned by ‘foreign’ advertising images regarded as a threat to the Malaysian culture. The regulatory authorities were most attentive to viewers’ complaints which influenced and reinforced their own (similar) concerns when examining television advertisements for screening.